Morally Animated: Toward a First-Year Seminar From the Person up. Issue 3 (3rd July 2019) - Cockle, Theodore F.
Abstract: The first-year seminar has historically been concerned with socializing students into collegiate life. As with any type of socialization, the first-year seminar perpetuates and is perpetuated by assumptions of "the good." Despite these moral assumptions, little research has discussed the first-year seminar in moral terms. In this article, I investigate the moral assumptions of first-year seminar research and practice to demonstrate the cost of failing to recognize the seminar as morally animated space. Following my analysis, I envision the first-year seminar from the person up.